SINTESIS LAPISAN TIPIS SENG OKSIDA DIDOPING PERAK (ZnO:Ag) DAN APLIKASINYA UNTUK PENDEGRADASI POLUTAN ORGANIK AIR - Sutanto, Heri; Nurhasanah, Iis; Hidayanto, Eko (BERKALA FISIKA, 2015)
Zinc Oxide (ZnO) is a semiconductor material that is used for photo-catalyst to degrade organic pollutants. The addition of doping silver (Ag) in ZnO can increase the photo-catalytic activity in the degradation process. In this study, the addition of doping Ag in ZnO thin film on a glass substrate deposition using thermal spray coating method has influence on the micro-structure and photo-degradation in presence of bacteria Escherichia coli (E. coli) as an organic pollutants has been investigated. Micro-structure of ZnO : Ag layer were characterized by Scanning Electron Microscopy (SEM) and photo-degradation activities of bacteria were tested with Total Plate Counter (TPC). The results show that doping Ag in ZnO give affect the topography of the surface that can increase in amount of grains and grain size in order to increase the photo-catalytic activity. It indicated by decrease in amount of E. coli bacteria from the initial sample with percentage of degradation is 99,99951% Keywords: Semiconductor, photo-catalyst, ZnO, doping Ag, micro-structure, photo-degradation